1985
DOI: 10.1093/ije/14.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Pollution and its Effect on Pulmonary Function of Adult Non-Smoking Women: III. Passive Smoking and Pulmonary Function

Abstract: The association between pulmonary function and exposure to tobacco smoke in the home was investigated in a sample of adult, non-smoking women living in a rural area. The women were all participants in a large longitudinal survey on the natural history and determinants of chronic non-specific lung disease. On cross-sectional analysis, several pulmonary function parameters were found to be significantly associated with exposure to tobacco smoke in the home. There was no association between exposure and pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 0 publications
1
24
0
1
Order By: Relevance
“…Mean daily duration of ETS exposure was 13 h. No significant difference could be demonstrated on FEV 1 , FVC, MEF 75 , and MEF 25 between the first and the 30th day of their imprisonment.…”
Section: Lung Function Testingmentioning
confidence: 82%
See 2 more Smart Citations
“…Mean daily duration of ETS exposure was 13 h. No significant difference could be demonstrated on FEV 1 , FVC, MEF 75 , and MEF 25 between the first and the 30th day of their imprisonment.…”
Section: Lung Function Testingmentioning
confidence: 82%
“…In particular, the older studies used spirometric tests of low sensitivity, such as FEV 1 and FVC, which depend mainly on the total airway resistance and elastic recoil of the lung, and are not disturbed even in the presence of early small airways dysfunction, possibly representing the initial reaction of the bronchopulmonary system to the active inhalation of tobacco smoke. However, many recent studies have assessed the potential effects of ETS on small airways function by means of sensible parameters, such as mean forced expiratory flow during the middle half of the forced vital capacity (FEF ) and the end of the FVC ( FEF [75][76][77][78][79][80][81][82][83][84][85].…”
Section: Lung Function Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Two other observational studies demonstrated a relation between ETS exposure and decreased forced expiratory flow, midexpiratory phase (FEF 25%-75% ), but not FEV 1 or FVC (35,36). Other investigators have found no consistent relationship between ETS exposure and pulmonary function in adults (37)(38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 98%
“…Numerous adverse health outcomes have been associated with long-term exposure to indoor air pollution during adulthood (8,18,20,66). These effects range from decreased cardiovascular health to chronic bronchitis and DNA damage.…”
Section: Indoor Air Pollutionmentioning
confidence: 99%